Gunshot Fracture of the Femoral Neck: Internal Fixation and Immediate Proximal Femoral Valgus Osteotomy. Issue 3 (July 2021) - Georgiadis, Gregory M.; Andrews, Kyle A.; Redfern, Roberta E.
Abstract : Case: We report on a 22-year-old patient with a comminuted femoral neck fracture because of a low-velocity gunshot wound. Treatment consisted of reduction and internal fixation with a fixed angled blade plate and immediate valgus osteotomy. He went on to uneventful healing and an excellent clinical result. Conclusions: A comminuted gunshot femoral neck fracture in a young patient is a rare and potentially devastating injury. If stable, and there are no other associated emergent injuries, reduction, internal fixation, and immediate valgus osteotomy should be considered.